Unveiling the Dynamic Between Land Conversion and Food Security of Farmers Households in Bakalan Village, Pasuruan Regency - Novianty, Puput Cindy; Soemarno, Soemarno; Efani, Anthon; Bushron, Raushanfikr (Universitas Diponegoro, 2024)
System Dynamics serves as an approach to unravel behavioral patterns by exploring fundamental structures. In this study, the dynamic system was crafted using STELLA software. The research methodology involved conducting primary surveys with both farmers and conversion farmers' households to gather essential data on their perspectives, practices, and circumstances related to land conversion and food security. Through this data, the System Dynamic model was constructed to depict the interplay among key variables impacting food security, specifically focusing on Food Availability, Affordability, and Needs. The analysis revealed that the Food Affordability indicator consistently played a pivotal role in shaping these trends over the analyzed years. However, a significant discrepancy in food security levels emerged between farming and non-farming households. This divergence primarily stemmed from income inequalities within the agricultural sector, affecting the purchasing power for essential foods like rice across the village. Additionally, a concerning trend of diminishing agricultural land and a subsequent decline in food availability was observed.